2001
DOI: 10.1592/phco.21.17.1325.34418
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk of Thrombocytopenia with Valproic Acid: Experience at a Psychiatric Teaching Hospital

Abstract: The estimated prevalence of thrombocytopenia is 12% in the general psychiatric population receiving VPA, with the elderly at greatest risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
1
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 20 publications
3
39
1
2
Order By: Relevance
“…In previous study, the reported frequency of VPA-induced thrombocytopenia has varied greatly and ranged from 0% to 32%. 7,10,[12][13][14][15][16][17][18][19] The strength of our study is that we conducted a longitudinal observational study in which the sequential assessment of platelets counts was done monthly to analyze the effect of VPA on platelet count.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous study, the reported frequency of VPA-induced thrombocytopenia has varied greatly and ranged from 0% to 32%. 7,10,[12][13][14][15][16][17][18][19] The strength of our study is that we conducted a longitudinal observational study in which the sequential assessment of platelets counts was done monthly to analyze the effect of VPA on platelet count.…”
Section: Discussionmentioning
confidence: 99%
“…The two studies have been published that attempt to identify the prevalence of this blood dyscrasia in the psychiatric population. 10,19,21 Some authors have seen that VPA-induced thrombocytopenia is dose-related, and usage of high doses can be considered as a potential risk factor. 22,23 It has also been reported that the VPA-induced thrombocytopenia resolves without interruption of VPA treatment that means thrombocytopenia is transient and shows self-resolving phenomena (increase in platelet count) which may predict that there is some hidden mediator for that transient recovery from thrombocytopenia in some subjects during the course of the study.…”
Section: Discussionmentioning
confidence: 99%
“…When we applied the 4Ts score 56 ( Table 2), it revealed 4 points (platelet count decrease .50% 5 2 points; onset of platelet count fall .day 10 5 1 point; no thrombosis 5 0 points; thrombocytopenia in a patient on a ventilator as an assumed other reason for thrombocytopenia 5 1 point), consistent with an intermediate risk for HIT, but the anti-platelet factor 4 (anti-PPF4)/ heparin immunoglobulin G (IgG) enzyme immunoassay was negative, thus ruling out HIT. 57,58 On the other hand, valproic acid is known to cause both immuneand non-immune-mediated thrombocytopenia 59 (Table 3). We stopped valproic acid while continuing all other medications, and the platelet count recovered (Figure 3).…”
Section: Managementmentioning
confidence: 99%
“…17,60,64 In contrast to DTP, DITP typically presents with an abrupt platelet count fall evolving within 1 to 2 days, which usually begins 5 to 14 days after starting a new drug, and a nadir below 20 3 10 9 /L, which is nearly always accompanied by mucocutaneous bleeding. 59,[65][66][67][68][69] Table 3 summarizes typical mechanisms and drugs of DTP and DITP. [61][62][63]65,70 More than 10% of patients treated with valproic acid develop DTP.…”
Section: Commentmentioning
confidence: 99%
“…[73,74] drugs (gold salts, penicillamine, sulfasalazine, Antibodies are subsequently formed, directed NSAIDs), [23][24][25][26][27]29,30,32,33,36,37,40] glycoprotein (GP) against this hapten-protein complex and ultimately IIb/IIIa receptor inhibitors, [35,41,43,[46][47][48] anticonvul-result in cell destruction. [74] Betalactam antibacterisants [49][50][51][52][53][54][55][56][57] and antibacterials such as cotrimoxazole als may also cause thrombocytopenia by a different and penicillin, [28,34,38,39,42] all of which are also mechanism, which possibly resembles the quinine mentioned in the systematic review of case re-type. [111] ports.…”
mentioning
confidence: 99%